ANALISIS MODEL HUBUNGAN SIKAP DAN NORMA SUBJEKTIF DENGAN NIAT BERWIRAUSAHA PADA MAHASISWA UNIVERSITAS UDAYANA - Wipraja, Pande Made Agus Surya; Piartini, Putu Saroyeni (E-Jurnal Manajemen; Vol 8 No 11 (2019), 2019)
The purpose of this study was to determine the intention of entrepreneurship students of Udayana University. The population and sample of this study were 450 students of Udayana University which consisted of 6 faculties representing the external and social fields namely the Faculty of Economics and Business, Faculty of Literature, Faculty of Law, Tourism, Faculty of Agriculture and the Faculty of Marine and Fisheries. The results of the analysis found that attitudes have a positive and significant effect on entrepreneurial intentions and subjective norms have a positive and significant effect on entrepreneurial intentions. From this study it can be concluded that subjective norms and attitudes influence the intention of entrepreneurship, the more the intention of entrepreneurship increases, the subjective norms and attitudes also increase. The next researcher can add other variables such as gender and environment. This is intended to obtain the strength of a clearer relationship regarding the correct variables capable of explaining an entrepreneurial intention in an institutional environment. Keywords : Attitudes, subjective norms, intention of entrepreneurship